APPLICATION OF FORECASTING TECHNIQUES AT ARIFCO PLASTIC FACTORY, JEDDAH, SAUDI ARABIA - Nehalah Baker Abuzenadah; Mohamed Baymout (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Forecasting is the use of historical data to predict event. ARIFCO is a plastic production company that is based in Jeddah. The company has a big difference between the actual sales and the target budget. Thus, this work was carried out to address the issue faced by ARIFCO. This work has analyzed and determined the best-fit method of forecasting for the sales of ARIFCO. This work has used qualitative and quantitative methods to find out the best forecasting method. Data from interviews and existing sales report were used to generate the findings. The sales in the Saudi Arabia region were focus for this study. Three forecasting methods namely exponential smoothing method, three moving average method and decomposition method was used in this work. The key findings of this work have shown that decomposition method has exhibited the best-fit method of forecasting with 1 % error. Thus, decomposition method will increase the revenue and reduce the losses of ARIFCO.